Bacteria‐Based Cancer Immunotherapy. Issue 7 (10th February 2021) - Huang, Xuehui; Pan, Jingmei; Xu, Funeng; Shao, Binfen; Wang, Yi; Guo, Xing; Zhou, Shaobing
Abstract: In the past decade, bacteria‐based cancer immunotherapy has attracted much attention in the academic circle due to its unique mechanism and abundant applications in triggering the host anti‐tumor immunity. One advantage of bacteria lies in their capability in targeting tumors and preferentially colonizing the core area of the tumor. Because bacteria are abundant in pathogen‐associated molecular patterns that can effectively activate the immune cells even in the tumor immunosuppressive microenvironment, they are capable of enhancing the specific immune recognition and elimination of tumor cells. More attractively, during the rapid development of synthetic biology, using gene technology to enable bacteria to be an efficient producer of immunotherapeutic agents has led to many creative immunotherapy paradigms. The combination of bacteria and nanomaterials also displays infinite imagination in the multifunctional endowment for cancer immunotherapy. The current progress report summarizes the recent advances in bacteria‐based cancer immunotherapy with specific foci on the applications of naive bacteria‐, engineered bacteria‐, and bacterial components‐based cancer immunotherapy, and at the same time discusses future directions in this field of research based on the present developments. Abstract : Bacteria‐based cancer immunotherapy has shown significant potential in the realm of tumor therapy, mainly because of bacterial specific targeting and preferential colonization of tumors, the abundant natural antigen library of bacteria, and the great engineerability. These high‐quality properties of bacteria have been and are being researched extensively, allowing the discovering of best immunotherapies.